A novel simulation model for development of renewable materials with waste-natural substance in sustainable buildings - Sagbansua, Lutfu; Balo, Figen (Elsevier Sci Ltd, 2017)
The sustainable materials back the trio of economy, environment, and energy because as a renewable source it has numerous positive affects on employment and it fuels the economic activities in the world. The building materials can be produced from sustainable sources recycled, re-used or harmlessly disposed on end use. In this paper, the thermal and mechanical characteristics of the insulation materials obtained from different waste (fly ash-FA) and natural (modified corn oil-MCO, perlite-P and clay-C) raw materials, as sustainable building wall's components are analyzed within the framework of a simulation model developed for the purpose of this research. A novel bio-composite material is obtained from these materials as its components. These materials' suitability as insulation materials for sustainable buildings is investigated through a software programme. For the period of January in Ankara province, the temperature distributions of the diverse wall types insulated together with only the Modified Corn Oil (MCO)-based block wall are evaluated with heat flow formulations by the ANSYS software programme. For this simulation, the construction-insulation material produced with the lowest thermal conductivity coefficient is applied to the diverse wall surfaces. This sustainable material's practicability is evaluated. It can be concluded that using fly ash-modified corn oil-perlite-clay in the specimen, allows obtaining a biocomposite with good mechanical and thermal characteristics, which can be used in structural components as a novel renewable material for energy performance in construction industry. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Thermo-mechanical properties; Vegetable oil; Sustainable building; Clean material; ANSYS software